Experimental Parameters Study Of Micro-Perforated Panel And The Application On Vacuum Cleaner - Ting, Kin Choon (Universiti Sains Malaysia, 2017)
Micro-perforated panel (MPP) are acoustic absorbers that are reclaimable, non-combustible, and environmentally friendly compared with traditional porous materials. The acoustic performance of MPP sound absorber depends on four major design parameters, such as perforation diameter, perforation ratio, air cavity depth, and thickness of the panel. In this experimental study, analysis of sound absorption coefficient of MPP sound absorber at constant thickness with different perforation diameter, perforation ratio and backing cavity were conducted by using transfer function method (impedance tube). The result showed that small perforation diameter 0.2mm give large acoustic resistance which turns to increase the overall sound absorption coefficient of MPP sound absorber. Then, the increase in the perforation ratio from 0.19% to 1.72% increased the sound absorption peak coefficient and shifted toward high frequency. The increasing in the backing cavity depth from 5mm to 30mm was shifted the sound absorption coefficient peak frequency to lower frequency range. Overall, the experimental result showed correlation agreement to Maa model. At the last of the paper, the parameter of MPP was optimized tuned by simulated annealing algorithm. Then, the optimized MPP sound absorber was applied to a small utility vacuum cleaner with power 1800W in order to prove the MPP in real life application and the results showed that the overall noise level reduced by 2.2dB(A) which is 2.69% from the overall operating noise of vacuum cleaner.